Evacuation and the politics of resistance in coastal communities in Tacloban City in the advent of Super Typhoon Yolanda - Lopez, Rizza Lynne C.; Santos, Katrina April S.; Santos, Paulynne M.; Saranza, Rhena B. (2015)
This study aims to reveal the multiple and underlying reasons why the coastal community residents resisted the evacuation orders in the advent of Super Typhoon Yolanda. Specifically, this study looks into the motivations that the coastal residents have in discrediting the evacuation orders.